Key models of classical European university and their impact on the development of National higher education: historical background - Yakunina, A. (New Collegium, 2023)
The new vectors of European integration of Ukrainian higher education, which have emerged in modern conditions and are rapidly developing, have fundamentally returned the interest of scientists to the history of European integration in education. First of all, it is about attempts to find out not only the influence of classical models of European universities on the national one, but also to find out the historical origins of the differences that exist between modern practices of university functioning. The well-known classical models of European universities were formed at the turn of the XIX – XX centuries and absorbed the peculiarities of political systems and socio-economic situation of European countries. Humboldt’s (German), responding to the needs of the state and society, was more focused on the development of science and practical training, while Napoleon’s (French) – on the specialists’ education, free choice of educational programs. Newman’s (English) model was focused on creating conditions for the formation of the student’s personality, his/her comprehensive development. Of course, over time the models have been transformed, but retained their historical orientation and emphasis. The modern model of the national university has a fundamentally different history of formation, because it was born under a different scenario, and the basis for development was different from Western European schools. The Ukrainian model was developed much later and was able to absorb the best from its predecessors, especially from the Humboldt model. Over time, a kind of mix was formed, but the national model and approaches to the organization of university life were influenced by the peculiarities of the historical development of the country. Today everything is reflected in the practice of university functioning, approaches to teaching methods, teachers and students’ behavioral models, relations between them.